Determinants of BSI mobile banking adoption intentions: DeLone & McLean and UTAUT Model integration with religiosity - Sholihah, Erlinda; Antari, Ika Septiana Windi; Rochimawati, Rizqi Fajar; Ulwiyyah (Asian Journal of Islamic Management (AJIM), 2023)
Purpose − This research aims to identify influencing factors on BSI mobile banking adoption intention by integrating the UTAUT and DeLone & McLean models and the role of religiosity variables.Methodology − This research used primary data from 150 Bank Syariah Indonesia customers who used mobile banking. The analysis method applied SEM PLS to assess the relation among exogenous and endogenous variables using SmartPLS software.Findings − The findings show that from the factors identified, Service Quality, Information Quality, Performance Expectancy, Effort Expectancy, Social Influence, and Religiosity are critical variables in BSI mobile banking adoption intention. Because these six factors significantly impact the intention of BSI Mobile Banking adoption.Implications − Our work helps stakeholders strategize and policy to offer more innovative and flexible production technologies. So, the bank must pay more attention to things that support the increasing performance of mobile banking to increase customer intentions in adopting BSI mobile banking.Originality − This research provides a theoretical contribution in integrating the UTAUT and DeLone & McLean models, including the role of religiosity variables in assessing the adoption intention factors of BSI mobile banking in Indonesian society.